BƯỚC ĐẦU XÁC ĐỊNH HÀM LƯỢNG MỘT SỐ KIM LOẠI NẶNG TRONG MÔI TRƯỜNG NƯỚC SÔNG HỒNG - Ngọc, Nguyễn Thị Bích; Quỳnh, Lê Thị Phương; Hương, Nguyễn Thị Mai; Thủy, Nguyễn Bích; An, Vũ Duy; Thủy, Dương Thị; Cường, Hồ Tú; Nga, Trần Thị Bích (Vietnam Journal of Science and Technology, 2015)
Environment quality, especially aquatic environment is increasingly being interested. TThis paper presents the initial results of the monthly observations for the period from January 2012 to December 2012 on some heavy metal contents in the Red River system at the four hydrological stations in Ha Noi, Hoa Binh, Vu Quang and Yen Bai. The monitoring results showed that heavy metal concentrations in the Red River water varied in a high range: Cu: 10 – 80 mg/l; Zn: 2 – 88 mg/l; Cr: 0,2 – 5,1 mg/l; Pb: 2 - 107 mg/l; Cd: : 2 – 12 mg/l; Mn: 2 - 35 mg/l; Fe: 160 – 950 mg/l. Most of the mean values of heavy metal contents at the four monitoring sites were lower than the ones of the Vietnamese standard limits for surface water quality, QCVN 08:2008/BTNMT. However, at several time during the observation period, the contents of some heavy metals such as Fe, Cd and Pb exceeded the Vietnamese standard limits. The results shows that the water quality of the Red River needs more be frequently and systhematically observed